The anti-actin drugs latrunculin and cytochalasin affect the maturation of spruce somatic embryos in different ways - Vondráková, Zuzana; Eliášová, Kateřina; Vágner, Martin (Plant science, 2014)
The role of the actin cytoskeleton in somatic embryo development was investigated using latrunculin B and cytochalasin D. Brief treatments (1h) with either drug at the start of maturation fragmented the actin in suspensor cells and/or depolymerized actin filaments in meristematic cells. The drugs targeted different cells: latB primarily affected the suspensor cells, but cchD damaged both suspensor and meristematic cells. Lethal damage to the meristematic and suspensor cells was observed when the drugs were applied throughout the maturation period, although the severity of this effect depended on their concentrations. The drugs' effects on the yield of mature somatic embryos were investigated by applying them to embryo cultures throughout the maturation period or for one week at three different points in the maturation process: immediately prior to the start of maturation, during the first week of maturation, and during the fourth week of maturation. The strongest effects were observed when the drugs were applied at the start of maturation. Under these conditions, latB destroyed the suspensors, eliminating the underdeveloped embryos that depend on them. This accelerated the development of embryos that were capable of separating from the suspensors. Thus, while the total number of embryos at the end of the maturation period was lower than in untreated control cultures, the surviving mature embryos were of high quality. cchD treatment at the start of maturation strongly inhibited embryo development. Drug treatment at the end of the maturation period did not significantly affect embryo development: latB caused no change in the yield of somatic embryos, but cchD treatment increased the number of malformed embryos compared to untreated controls.
Keywords: Bridged Bicyclo Compounds, Heterocyclic; Thiazolidines; bicyklické sloučeniny heterocyklické; Picea; Somatic embryogenesis; Cytochalasin D; Microscopy, Confocal; aktiny; inhibitory syntézy nukleových kyselin; konfokální mikroskopie; Plant Somatic Embryogenesis Techniques; somatická embryogeneze rostlin; Seeds; cytochalasin D; thiazolidiny; Picea abies; Actins; smrk; Actin; Nucleic Acid Synthesis Inhibitors; Cytoskeleton; semena rostlinná